Le rôle de la vérification de conformité environnementale dans la fixation des primes d’assurance de responsabilité - Mercure, Pierre-F. (Assurances)

(untitled) (HEC Montréal, 1988)
Insurers and Company Managers have always been reluctant to deal with environmental risk. Environmental auditing is a means to evaluate the risk in order to establish more easily insurance premiums. For enterprises, it also has many advantages as it leads to a better management of environmental issues, helps minimize liabilities and contributes to lower insurance premiums. New Federal legislation on environmental protection will encourage company managers to incorporate environmental auditing into their regular activities.